Dynamics of power in Dutch integration politics from accommodation to confrontation - Uitermark, Justus 1978- (Amsterdam University Press, 2012)
Integration politics in the Netherlands has changed dramatically between 1990 and 2005. Whereas ethnic and religious differences were hitherto pacified through accommodation, a new and increasingly powerful current in Dutch politics problematizes-the presence of minorities. This development represents a challenge to sociologists and political scientists: how to map and explain drastic changes? Arguing that extant approaches are better at explaining continuity than change,-this book-develops a distinct approach to the study of dynamic power relations to understand drastic transformations in the national debate as well as urban governance
Keywords: Geschichte 1990-2005; Minorities / Netherlands; Immigrants / Government policy / Netherlands; Political participation / Netherlands; Multiculturalism / Netherlands; Einwanderer; Zivilgesellschaft; Soziale Integration; Niederlande